Bagaimana Pengetahuan Kewirausahaan Mempengaruhi Minat Berwirausaha Generasi Z melalui Efikasi Diri? - Muhammad Hasan; Nur Shofa; Ilham Thaief; M. Ihsan Said Ahmad; Thamrin Tahir (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to explore the contribution of entrepreneurial knowledge to the formation of Generation Z's entrepreneurial interest through self-efficacy. This study is a study with a quantitative approach. The population of this study is all generation Z in class XI of SMK Negeri 7 Pangkep, South Sulawesi with a total of 131 generations with a purposively drawn sample of 57 people with several criteria. The data in this study were collected using questionnaires and interviews. This study consists of 3 variables consisting of entrepreneurial knowledge, entrepreneurial interest, and self-efficacy. Data analysis used path analysis technique. The findings of this study indicate that entrepreneurial knowledge has a positive and significant effect on the self-efficacy of Generation Z. In addition, there is also a positive and significant effect of self-efficacy on the interest in entrepreneurship of Generation Z. Other findings indicate that entrepreneurial knowledge has a positive and significant influence on Generation Z's entrepreneurial interest, and finally it was found that entrepreneurial knowledge has a positive and significant effect on entrepreneurial interest through Generation Z's self-efficacy.